2004
DOI: 10.1177/1038411104048172
|View full text |Cite
|
Sign up to set email alerts
|

On international assignment: Is expatriation the only way to go?

Abstract: This research explored variations to traditional international assignment. Interviews with expert informants and a survey of 43 human resource managers investigated whether or not four categories of international assignment identified in a recent European survey are occurring in Australian‐based multinational enterprises (MNEs). The findings presented are illuminating, but not generalisable. It seems that within this group, a portfolio of international assignment options, in addition to expatriation, is increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 12 publications
0
23
1
Order By: Relevance
“…Some researchers have argued that IBTs do not come under the remit of alternative forms of international assignments as, they do not involve physical relocation to a different country (Welch and Worm, 2006). However, following Fenwick (2004) we include them in our discussion because the evidence suggests that they are an important alternative to the traditional expatriate assignment for MNCs (Michailova and Worm, 2003). IBTs provide the advantage of face-to-face interaction in conducting business transactions without the requirement for their physical relocation.…”
Section: Frequent Flyer Assignmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have argued that IBTs do not come under the remit of alternative forms of international assignments as, they do not involve physical relocation to a different country (Welch and Worm, 2006). However, following Fenwick (2004) we include them in our discussion because the evidence suggests that they are an important alternative to the traditional expatriate assignment for MNCs (Michailova and Worm, 2003). IBTs provide the advantage of face-to-face interaction in conducting business transactions without the requirement for their physical relocation.…”
Section: Frequent Flyer Assignmentsmentioning
confidence: 99%
“…However research suggests there is little evidence of a significant decline in the use of long-term assignments but does identify the growing use of alternative forms of international assignments (cf. Dowling and Welch, 2004;Fenwick, 2004;Mayerhofer et al, 2004;PriceWaterhoseCoopers, 2005;Scullion and Collings, 2006c;Tahanainen, Welch and Worm, 2005). A recent survey reported that 62 per cent of respondents suggested that their organizations were seeking alternatives to long-term assignments (GMAC, 2005).…”
Section: Alternative Forms Of International Assignmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can take the form of obligatory and frequent breaks to their country of origin. Many MNCs include regular return trips home for expatriates (Fenwick, 2004) but this is not characteristically part of the inpatriate contract which is typically longer-term (Harvey et al, 2000). We maintain that, in order to encourage integration, it is important to ensure that the inpatriate maintains her/his culture of origin.…”
Section: Encourage a Hybrid Cultural Positionmentioning
confidence: 94%
“…Alternatively, a number of research questions were generated to guide and focus the research process (Stahl, Miller & Tung, 2002;Fenwick, 2004). The research questions were developed based on an extensive review of the literature and cover areas of self-initiated expatriation (Inkson, Pringle, Arthur & Barry, 1997;Sutari & Brewster, 2000;Tharenou, 2003;Vance, 2005), women expatriates (Adler, 1994;Linehan, Scullion & Walsh, 2001;Paik & Vance, 2002;Fischlmayr, 2002;Crowley-Henry & Weir, 2007), global careers and career development (Thomas, Lazarova & Inkson, 2005;Bolino, 2007;Tarique, Schuler & Gong, 2007;Vance, 2005) as well as literature on issues of discrimination (Richardson, 2006;Tzeng, 2006 …”
Section: Introductionmentioning
confidence: 99%